Digestibility and nitrogen balance of lambs fed sugarcane hydrolyzed under different conditions as roughage in the diet - Endo, Viviane; Sobrinho, Américo Garcia Da Silva; Almeida, Fabiana Alves de; Lima, Natália Ludmila Lins; Zeola, Nivea Maria Brancacci Lopes (Universidade Federal de Santa Maria, 2015)
This study aimed to evaluate the digestibility and nitrogen balance (NB) of lambs fed sugarcane hydrolyzed under different conditions. Fifteen Ile de France lambs at, on average, 23.5kg of body weight were evaluated. Treatments were: in natura sugarcane (IN), sugarcane hydrolyzed using 0.6% calcium oxide (CaO) under aerobic condition (AER), and sugarcane hydrolyzed using 0.6% CaO under anaerobic condition (ANA). Therefore, a completely randomized design was constituted with five replicates per treatment. Treatments were supplied to animals along with concentrate. Both hydrolysis conditions aimed to alter the sugarcane fermentation pattern, therefore improving fiber digestibility. Lambs were housed in individual pens and fed with diet allowing 10% of refusals. Refusals, feces and urine were sampled daily during five days. They were collected to determine the digestibility and NB. A higher digestibility of neutral detergent fiber corrected for ash and protein (57.05%), organic matter (85.39%), hemicellulose (72.09%), NB (29.46g day-1 and 2.78g kg-0.75 day-1) and rate of nitrogen absorbed (3.00g kg-0.75 day-1) were observed for lambs fed with ANA than for those fed IN (41.17%, 73.76%, 53.80%, 21.39g day-1, 2.00g kg-0.75 day-1 and 2.22g kg-0.75 day-1, respectively). As roughage, ANA in the lamb diet, optimizes the nitrogen balance and is more efficient to improve the digestibility of some nutrients compared to IN. Whereas AER was as efficient as ANA and IN

O objetivo deste estudo foi avaliar a digestibilidade e o balanço de nitrogênio (BN) do volumoso cana-de-açúcar hidrolisada sob diferentes condições, na alimentação de cordeiros. Foram utilizados 15 cordeiros Ile de France, em média, com 23,5kg de peso corporal. Os tratamentos foram: cana-de-açúcar in natura, cana-de-açúcar hidrolisada com 0,6% de óxido de cálcio (CaO), sob condição aeróbica e cana-de-açúcar hidrolisada, com 0,6% de CaO, sob condição anaeróbica, constituindo um delineamento inteiramente casualizado com cinco repetições por tratamento. Os tratamentos foram fornecidos aos animais, juntamente com o concentrado. Ambas as condições das hidrólises tiveram o intuito de alterar o padrão de fermentação da cana-de-açúcar e, com isso, melhorar a digestibilidade de suas fibras. Os cordeiros foram confinados em baias individuais e a dieta foi fornecida permitindo 10% de sobras. Estas sobras foram amostradas diariamente por cinco dias, bem como as fezes e urina foram coletadas para determinar a digestibilidade e o BN. Foi observado, para cordeiros alimentados com ANA, maior digestibilidade da fibra em detergente neutro, corrigido para proteína e cinzas (57,05%), matéria orgânica (85,39%), hemicelulose (72,09%), maior BN (29,46g dia-1 e 2,78g kg-0,75 dia-1) e taxa de nitrogênio absorvido (3,00g kg-0,75 dia-1), em comparação ao IN (41,17%, 73,76% e 53,80%, 21,39g dia-1, 2,00g kg-0.75 dia-1 e 2,22g kg-0.75 dia-1, respectivamente). Como volumoso, ANA otimiza o balanço de nitrogênio e é mais eficiente em melhorar a digestibilidade de alguns nutrientes, comparado à IN. AER tão eficiente quanto ANA e IN
Digestibilidade e balanço de nitrogênio em cordeiros alimentados com cana-de-açúcar hidrolisada em diferentes condições como volumoso na dieta
Keywords: condição de hidrólise; fibra em detergente neutro; nitrogênio retido; condition of hydrolysis; neutral detergent fiber; nitrogen retained